Plastics technology handbook - Chanda, Manas (Plastics engineering (Marcel Dekker, Inc.), 1993)
Provides examinations of the chemical nature, characteristic properties, and uses of traditional industrial polymers and offers coverage of specialty polymers designed to satisfy specific applications. This edition contains sections on antioxidants and related compounds.